Revealing the Practice of the Shadow State in the Bureaucratic System of the Manokwari Regency Government - Marcelino Solissa (JGov: Journal of Governmentality, 2026)
This study examines the practice of the Shadow State within the bureaucratic governance system of the Manokwari Regency Government. Bureaucratic governance plays an essential role in ensuring effective public administration and regional development. However, the bureaucratic system may become vulnerable when informal actors outside formal state institutions exert significant influence over governmental processes. This study uses a qualitative approach through literature review and analysis of local political dynamics. The findings reveal that the practice of the Shadow State in Manokwari Regency emerged from the early stage of the regent’s administration and was strengthened through informal political networks, kinship relations, and the utilization of individual political capital. Shadow state actors were able to dominate certain bureaucratic authorities through close relationships with formal state actors. The case of Jimmi Ell, who gained strategic influence as a special staff member to the Regent of Manokwari, demonstrates how informal authority can shape legal and administrative processes within local government. The study concludes that Shadow State practices strengthen patron-client politics, weaken bureaucratic neutrality and accountability, and create opportunities for informal elites to consolidate power in local politics in Indonesia.